Examining the Role of FII Derivatives Trading Activities in Managing Risk in the Indian Stock Market - Babu, Abin (Digital Repository of Theses - SSBM Geneva, 2025)
This dissertation examines the role of Foreign Institutional Investors (FIIs) in managing risk through derivatives trading in the Indian stock market. The research employs a mixed-methods approach, integrating econometric modeling and thematic analysis, to evaluate the dual function of derivatives as risk mitigators and market influencers. Key findings reveal that derivatives trading by FIIs enhances liquidity and aids price discovery while simultaneously contributing to short-term market volatility, especially during speculative periods. Regulatory and macroeconomic factors, including SEBI policies and currency fluctuations, significantly shape FII trading strategies. This study underscores the need for balanced regulatory frameworks that optimize the benefits of foreign investment while minimizing systemic risks, contributing to academic and practical insights into market dynamics in emerging economies like India